2020
DOI: 10.3390/jcm9020360
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acids in the Treatment of Most Lethal Solid Cancers

Abstract: Although the use of oral administration of pharmacological all-trans retinoic acid (ATRA) concentration in acute promyelocytic leukaemia (APL) patients was approved for over 20 years and used as standard therapy still to date, the same use in solid cancers is still controversial. In the present review the literature about the top five lethal solid cancers (lung, stomach, liver, breast, and colon cancer), as defined by The Global Cancer Observatory of World Health Organization, and retinoic acids (ATRA, 9-cis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 246 publications
(280 reference statements)
2
42
0
Order By: Relevance
“…Instead, among the up regulated proteins, beyond those implicated in the metabolism of proteins and in the post-translation protein modifications, obviously necessary to proliferation, others involved in the regulation of IGF transport and uptake by IGFBPs, and in the RAF/MAP kinase cascade were found. IGF exerts a pro-survival action stimulating the PI3k/Akt pathway, and other evidence in the literature showed that in ATRA-sensitive cancer cells, ATRA suppresses IGFs proliferative action, whilst in ATRA-resistant cell lines the IGFs proliferative action occurs for several modified molecular mechanism [4]. In support of this data, previous papers showed the up regulation of the IGFs proliferation pathway in T24 cells in comparison to normal urothelial cells [17,18].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Instead, among the up regulated proteins, beyond those implicated in the metabolism of proteins and in the post-translation protein modifications, obviously necessary to proliferation, others involved in the regulation of IGF transport and uptake by IGFBPs, and in the RAF/MAP kinase cascade were found. IGF exerts a pro-survival action stimulating the PI3k/Akt pathway, and other evidence in the literature showed that in ATRA-sensitive cancer cells, ATRA suppresses IGFs proliferative action, whilst in ATRA-resistant cell lines the IGFs proliferative action occurs for several modified molecular mechanism [4]. In support of this data, previous papers showed the up regulation of the IGFs proliferation pathway in T24 cells in comparison to normal urothelial cells [17,18].…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, also proteins of the RAF/MAP kinase pathway turned out to be up-regulated following ATRA treatment in T24 cells. Also in this case, RAF/MAP kinase pathway is inhibited by ATRA treatment in ATRA-sensitive cells, but in ATRA-resistant this pathway is functional and through c-jun and c-fos lead to cellular proliferation [4]. However, the molecular mechanisms by which ATRA up or down regulated the described pathways in T24 cells need to be investigated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In combination with chemotherapy or arsenic trioxide, ATRA is used in the treatment of acute promyelocytic leukemia with outstanding results, inducing long-term remission in the majority of patients [ 14 ]. The therapeutic activity observed in this type of acute leukemia has raised interest in the use of ATRA and derived synthetic retinoids for the personalized management of solid tumors, including breast cancer [ 15 ]. In this last context, a substantial number of pre-clinical in vitro and in vivo results indicate that ATRA is a promising agent in the treatment/chemo-prevention of mammary tumors [ 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%